Toward Multi-Level Governance in China? Coping with complex public affairs across jurisdictions and organizations. (April 2019) - Ongaro, Edoardo; Gong, Ting; Jing, Yijia
This special issue argues for the applicability of the conceptual framework of Multi-Level Governance to the political–administrative regime of China, provided significant adaptations and qualifications are developed. The application of Multi-Level Governance to China enables to account for global influences as well as for the involvement of non-governmental actors in public policy making. More radically, we suggest in this introductory article that the development of Multi-Level Governance may be interpreted as a way of enhancing the societal legitimacy of the political regime under the conditions of new authoritarianism. We conclude this article by drawing a fascinating yet possibly hazardous and overstretched parallel; that is, the development of Multi-Level Governance may be part and parcel of a process of building political legitimacy in China, just as it may be a way of exploring paths for the renewal of beleaguered traditional liberal democracy in Europe. Albeit along profoundly different trajectories, China and Europe might adopt Multi-Level Governance arrangements for a very purposive course of action: enhancing the legitimacy of the respective and very diverse political systems and buttressing their very foundations. This suggests a strongly normative and purposive application of Multi-Level Governance.